Soil compaction level under mechanized harvesting system in paddy field: a comparisons of pre-harvest and post-harvest / Mohamad Aiman Muslim Mohamad Sakri - Mohamad Sakri, Mohamad Aiman Muslim (Faculty of Plantation and Agrotechnology, 2019)
Soil compaction is a serious problem which can lead in increasing of soil erosion and decreasing of crop production. This happen due to the compression soil density and reduction on the size of pores space by eliminating the water contents. This study was conducted to measure the soil compaction levels in paddy field conditions before and after of harvesting operation. The measurements used a penetrometer to evaluate the soils compaction in Kampung Sempang, Merlimau paddy fields. Prior the testing, sampling points was made on the areas with 9 quadrants and 5 samples were taken on each quadrant. While testing, the penetrometer was pressed steadily and evenly into the soil to make sure the data received are accurate. Besides, soil samples also were taken to the laboratory to identify the soil moisture. Data obtained were analyzed using SPSS and Excel to investigate the comparison, correlation and regression. The findings found that, there were relationship between soil moisture and soil compaction showed the significant differences on compaction levels before and after rice harvesting processes with differences value of 9.111 lbs where soil compaction level after harvest operation was greater than that before harvest. The mechanization in paddy harvesting influences the destruction on soil moisture and compaction of soil in paddy land in long term of utilization.